Perancangan Desain Terowongan Pelimpah (Spillway) Bendungan Bulango Ulu Menggunakan Tabel Beggs - askur, wahyu; Kadarningsih, Rahmani (Jurnal Teknologi Berkelanjutan, 2025)
A tunnel is a tunnel beneath the surface of a mountain or land with both ends open as an entry portal and an exit portal. Based on this, it is necessary to design the spillway tunnel using the Beggs Deformation Stress Table . The design of the spillway tunnel for the Bulango Ulu Dam was designed using a horseshoe shape, Shape B. The tunnel loading was calculated using 10 forms of loading, namely vertical rock pressure, normal horizontal rock pressure, earthquake horizontal rock pressure, horizontal water pressure, vertical water pressure, pressure due to its own weight, water pressure in the tunnel, uplift pressure, horizontal saturated rock pressure, vertical saturated rock pressure. The results of the load calculations are carried out by calculating load combinations with 10 combinations, namely normal conditions, earthquake conditions, normal filling conditions, earthquake filling conditions, normal operating conditions of a fully filled tunnel, earthquake operating conditions of a fully filled tunnel, normal operating conditions of a partially filled tunnel, earthquake operating conditions. the tunnel is partially filled, normal operating conditions the tunnel is empty, earthquake operating conditions the tunnel is empty. From the results of the load combination calculations, moment calculations were carried out using the Beggs Table . The maximum moment is selected for tunnel reinforcement calculations